Knowledge and practices of households on safe water chain maintenance in a slum community in Kampala City, Uganda - Charles Ssemugabo; Solomon Tsebeni Wafula; Rawlance Ndejjo; Frederick Oporia; Jimmy Osuret; David Musoke; Abdullah Ali Halage (Komiyama Printing Co. Ltd, 2019)
Abstract Background More than half of the disease burden in Uganda can be prevented through improving water, sanitation, and hygiene (WASH). In slum communities, water supply is insufficient but also highly contaminated; therefore, ensuring that the safe water chain is maintained by households is paramount to preventing water-related diseases. This study aimed at assessing knowledge and practices of households on safe water chain maintenance in slum communities in Kampala City, Uganda. Methods This was a community-based cross-sectional study carried out among 395 households in slum communities in Kampala, Uganda. Data were collected using a semi-structured questionnaire. Prevalence ratios (PRs) and their 95% confidence intervals were used as a measure of association between safe water chain management and associated knowledge and practice factors. The PRs were obtained using a multivariable modified Poisson regression with logarithm as the link function, with robust standard errors. Results Majority (76.7%, 303/395) of the households collected their water from a piped water system and paid for the water (72.9%, 288/395). Almost all (97.2%, 384/395) of the participants said that they knew the dangers associated with drinking unsafe water, boiled their drinking water (95.4%, 377/395), and used storage containers that minimize contamination (97.0%, 383/395). However, only (32.4%, 128/395) of the households satisfactorily maintained the safe water chain. Female- (adjusted PR = 1.82, 95% CI (1.19-2.78)) and student-led households (adjusted PR = 1.58, 95% CI (1.03-2.41)) and those whose heads had attained post-primary education (adjusted PR = 1.48, 95% CI (1.02-2.17)) were more likely to satisfactorily maintain the safe water chain. This was similar among members who thought most contamination occurs during storage (adjusted PR = 1.47, 95% CI (1.10-1.97)). Conclusion Only a third of the households maintained the safe water chain satisfactory. Female-led, student-led, and post-primary educated-led household and household that thought most contamination occurs during storage were more likely to maintain the safe water chain. There is a need to improve the level of awareness about the importance of the safe water chain among slum dwellers.